Exploring Pre-Service Teachers’ TPACK Competence during Teaching Practicum - Ahmada, Adib; Mahmud, Moh (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
This study investigates the Technological Pedagogical Content Knowledge (TPACK) competence of five pre-service teachers during a one-month teaching practicum at MTs N 2 Banyuwangi. The study aimed to measure their overall TPACK competence and identify which domain is strongest and weakest. A descriptive quantitative design was employed using a 15-item self-assessment questionnaire on a 5-point Likert scale, complemented by document analysis of lesson plans, teaching materials, and reflective reports. The findings show that the participants demonstrated a generally high level of TPACK, with CK emerging as the strongest domain, followed by PK, whereas TK remained the weakest. The integrative TPACK score suggests that the pre-service teachers possessed moderate confidence in combining technology, pedagogy, and content during instruction. Document analysis further supported these findings by confirming strong content mastery and adequate pedagogical preparation, while also revealing limited integration of digital tools in classroom practice. These findings highlight the need for more structured technological training and earlier exposure to educational technology within teacher education programs to strengthen pre-service teachers’ technological competence.